VIOLENCE AGAINST WOMEN DURING COVID-19 IN BANGLADESH - Chowdhury, Md. Mahabub (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
COVID-19 has become one of the biggest humanitarian crises affecting millions of lives around the world. Bangladesh is also affected by the COVID-19 crisis. Society, health, and economic sectors of Bangladesh are affected by this pandemic. Violence against Women is also common in Bangladesh. This study discusses the trends of violence against women in Bangladesh during the COVID-19 pandemic. The prevailing gender norms, patriarchy, and socio-economic factors made women of Bangladesh vulnerable to different forms of gender-based violence. Women face different types of gender-based violence such as rape, domestic violence, dowry-related violence, sexual harassment, and stalking. The objective of the study is to find out the trends of violence against women during COVID-19, underlying factors behind such acts, and the consequences of such violence on women’s lives. The study is done using qualitative research techniques. In-depth interview, Key Informant Interview (KII), document analysis techniques were used to collect data. This study found that socio-cultural factors and prevailing gender norms played a significant role in the spike of violence against women during the pandemic causing extreme social, psychological, economic, and health harm to women. JEL Classification Codes: K42, K38, N35.